Evaluasi Pengelolaan Dana Desa Dalam Meningkatkan Pembangunan Fisik Desa Banjaranyar Kecamatan Brebes Kabupaten Brebes - Nurul Mahmudah; Yusri Anis Faidah (Jurnal Portofolio : Jurnal Manajemen dan Bisnis, 2023)
The capacity of village officials as policy implementers is a supporting factor for the successful implementation of programs financed by the Village Fund. The abilities and skills of the village apparatus as implementers of policies are the basis of governance implementation. The competence of human resources in implementing the Village Fund policy is felt to be inadequate. This condition has an impact on the lack of effectiveness of program implementation, then other problems such as village officials who do not understand budget planning and execution, the disbursement process is too long and the accountability report process is complicated so that it has an impact on the incompatibility of priorities and non-priority planning of work programs made by Programs development programs originating from the Village Fund that focus on physical development have been running and have physical evidence, for example the construction of Normalization of canals and widening of farm roads, but these developments are felt to have no impact on all village communities. On the other hand, the problem that arises is the lack of outreach the Village Fund policy so that it does not touch the community which is the direct executor of the various programs funded. Lack of socialization has an impact on the lack of community participation to provide suggestions about what programs are urgent, as well as the low knowledge of village communities about village programs.